Dependence of microstructural evolution on the geometric structure for serviced DZ125 turbine blades - Xie, Yadan; Zhao, Jianjiang; Fu, Haoran; Wei, Hua (Frontiers in Materials, 2023)
The turbine blades were directionally solidified by a high rate solidification (HRS) process by the Bridgman technique using directional solidified (DS) Ni-based master superalloy DZ125 and operated on the engine bench with the high-temperature gas environment of more than 1500℃ from combustor and high speed rotation of more than 13500rpm for 400 hours. A service-environment based model was put forward to simulate the distribution of temperature and stress on DZ125 blade in service. It was found that the distribution of temperature and stress on serviced DZ125 blade were closely related to its geometric structure. The microstructural evolution of serviced DZ125 blade was analyzed and the variations of microstructures with temperature and stress were investigated by scanning electron microscope. The results revealed that the evolution process of microstructures on serviced DZ125 blade was different from that of the standard sample tested at constant temperature and uniaxial tensile stress. The reason for this discrepancy was explored using a combination of finite element calculation and diffusion coefficient calculation.